FIKISMART: Website-Based Learning Media for Islamic Religious Education Subjects, Topic of Fiqh for Middle Schools - Zulfa, Laila Ngindana; Azhari, Ni'am; Irvan Fuadi, Salis; Lestari, Prawidya; Khoirul Ulumuddin, Imam (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
In the increasingly advanced digital era, the use of information technology-based learning media is very relevant and important. Given the gap between students' needs for interactive and innovative learning media and teaching methods that still tend to be conventional in Islamic Education (PAI) subjects. This study aims to examine the feasibility of developing Islamic Religious Education (PAI) learning media based on the website "FIKISMART" in the context of Fiqh Mawaris learning at the Junior High School (SMP) level. Therefore, this study uses the Research and Development (R&D) method to explore the needs of students and teachers in Fiqh Mawaris learning. Through qualitative data collection (Needs analysis and feasibility for teachers) and quantitative (Needs analysis, Validity (Material and Media Experts) and feasibility for students). The results of the study at the needs analysis stage showed that 54% of students answered "agree" which showed that website-based learning media was feasible to be developed. Furthermore, the researcher compiled a prototype of interactive and informative learning media. The results of the validity test showed that the "FIKISMART" learning media was proven valid with a score of 91% by material experts and 93% by media experts. From the feasibility test, "FIKISMART" has significant potential to be developed and used, especially to improve students' understanding of Fiqh Mawaris material. By considering the aspects of usability, relevant content, and high interactivity, this media is expected to provide a more enjoyable and effective learning experience.